Mollusk or Triton? Poetic Imagery of Joseph Brodsky’s “Great Poem” - O. V. Bogdanova; T. N. Baranova (Научный диалог)
This article presents a new interpretation of Joseph Brodsky’s “Great Poem” titled “Triton” (1994, originally named “Mollusk”) and its titular imagery. It is noted that previous scholars have exclusively interpreted the titular image metaphorically, relying on the poem’s poetic imagery and allusively linking the mollusk and triton images to the symbolism of the marine element or, more concretely, to the historical and architectural context of the poem. This study adopts a different approach, suggesting a connection between the poem’s creation and real events in Brodsky’s life, particularly a heart attack he experienced shortly before writing. It demonstrates that the image of the mollusk has a specific source of metaphorization in Brodsky’s work — the human heart, which, like a living mollusk, opens and closes its valves, filling its chambers, and is intricately linked to the vital aorta. The article traces how seemingly incidental “medical” details accumulate additional connotations, providing semantic and meaningful support for the entire poetic structure. Various reasons and origins for the change in the poem’s title and the transformation of its titular imagery are proposed. It is shown that the “mystery” of the titular image in Brodsky’s poem possesses both existential and quotidian dimensions. The authors note that the context of Soviet literature in which the poet was formed did not hinder him from creating a profound philosophical work.